Optimizing Paylater Service Design with Service Quality Approach Using Factor Analysis and Analytical Hierarchy Process Methods - Intan Sari , Debrina; Putranta, A.A. BGS Dinariyana Dwi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The automotive business is one of the businesses that experienced a difficult time during the Covid pandemic and gradually increased after the pandemic along with the increasing need for transportation. The aftersales service business has a considerable revenue contribution to the company, but the competition in this business is very tight, considering the cost of service at authorized workshops is more expensive compared to non-authorized workshops. To increase people's interest in using the after-sales service at PT Astra Isuzu, transformation is needed related to service, service quality and payment channel. PT Astra Isuzu already has an e-wallet called AstraPay, which works together with Maucash paylater. However, this digital payment platform has not been utilized as a payment channel for aftersales service. This research aims to identify and prioritize customer needs related to paylater payment methods. The method used in this research consists of 2 (two) stages, namely factor analysis and Analytical Hierarchy Process (AHP). The factor analysis method is used to determine the factors that have a positive and significant effect on interest in using paylater by identifying and measuring factors that are thought to have an effect. Furthermore, these factors are made into quality dimensions through Service Quality. While the AHP method is used to determine the priority ranking of the results of factor analysis by weighting. So that the results of factor analysis will be the basis for determining criteria in the AHP method. Data collection in this study used a questionnaire method with respondents being Isuzu vehicle service users. Focus group discussion was also conducted by involving the management of PT Astra Isuzu. By using factor analysis method, it was found that from 15 indicators were reduced to 9 indicators which were grouped into 3 components or factors. Furthermore, for the 9 indicators, AHP weighting was carried out, in which the 3 most important priorities for paylater design were the speed of handling customer complaints, Service Advisor providing information about paylater to customers and followed by a smooth and stable internet network at Astra Isuzu.